Structure and mapping of antigenic domains of protein antigen b, a 38,000-molecular-weight protein of Mycobacterium tuberculosis. - Andersen, A B (1989)
Only a limited number of proteins from Mycobacterium tuberculosis have so far been shown to possess species-specific epitopes as defined by monoclonal antibodies. One such protein is protein antigen b (Pab) of molecular weight 38,000, which binds the monoclonal antibodies HYT 28, HAT 2, HBT 12, HGT 3, TB 71, and TB 72. The gene encoding this protein was isolated from a lambda gt11 M. tuberculosis DNA library. The nucleotide sequence of the recombinant mycobacterial insert was determined, and an open reading frame of 374 amino acids was identified. The amino acid sequence exhibited 30% homology to a phosphate-binding protein, PstS, from Escherichia coli. The pab gene was subcloned into pBR322 in conjunction with the lacZ gene, and deletions were obtained from the 3' end. The anti-Pab monoclonal antibodies were used to probe crude protein lysates of E. coli transformed with the deletion plasmids. The monoclonal antibodies showed two reactivity patterns; one group of antibodies were dependent on the presence of the ultimate 91 amino acids of the protein, whereas another group of antibodies recognized an antigenic domain located on the middle portion of the molecule. None of the antibodies bound to the N-terminal 117-amino-acid peptide.